Towards a just transition: unpacking the gender differences in household cleaner energy use - Jayasinghe, M.; Best, R.; Selvanathan, E. A.; Selvanathan, S. (Elsevier, 2025)
Energy transition intersects between many of the United Nations' Sustainable Development Goals. Lack of access to cleaner energy is a main concern of injustice in energy transition policy. Women, especially in developing countries, disproportionately endure the negative consequences of lack of access to cleaner energy particularly in relation to health, education and economic participation outcomes. This study, using four waves of Household Income and Expenditure survey data (2006/07, 2009/10, 2016 and 2019), examines the gender differences in domestic cleaner energy use in Sri Lanka, with a special emphasis on cleaner energy use gap across de-jure and de-facto female-headed households (FHHs). To provide deeper insights into gender differences in cleaner energy use, we utilise the Exogenous Switching Treatment Effect Regression (ESTER) estimation method and the Fairlie decomposition technique. The results indicate that significant differences exist between male-headed households (MHH) and FHH for cooking and lighting approaches among Sri Lankan households. MHH are less likely to use cleaner energy sources for cooking but more likely to use solid cooking fuel when headship-based heterogeneities are taken into consideration. The cleaner-cooking difference between MHH and FHH is most pronounced as assets grow. De-jure FHH are more likely than de-facto FHH to use transitional cooking.